Policies to support women's paid work - Gianna Claudia Giannelli (IZA World of Labor, 2015)
Engaging in paid work is generally difficult for women in developing countries. Many women work unpaid in family businesses or on farms, are engaged in low-income self-employment activities, or work in low-paid wage employment. In some countries, vocational training or grants for starting a business have been effective policy tools for supporting women's paid work. Mostly lacking, however, are job and business training programs that take into account how mothers' employment affects child welfare. Access to free or subsidized public childcare can increase women's labor force participation and improve children's well-being.
Keywords: I25; J13; J16; J22; J61; O15; 330; female employment; paid work; vocational training; cash grants; child well-being